Graphic Design Course in Multidisciplinary Education in Arabic Language and Literature Study Programme: A Phenomenological Study of Lecturer Experience - Roziki, Khafid; Abidin, Munirul; Syuhadak, Syuhadak (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
The integration of graphic design skills in the curriculum of the Arabic Language and Literature (BSA) Study Program is one of the strategic steps in preparing graduates who are able to compete in the era of globalisation and digitalisation. This study aims to explore these challenges and identify innovative strategies applied by lecturers in teaching graphic design in BSA. Using a qualitative approach based on phenomenology, data was collected through interviews with lecturers teaching Graphic Design courses. The data were analysed and combined with relevant academic literature to provide a theoretical foundation on multidisciplinary approaches in higher education. The results showed that the main challenges in teaching graphic design in BSA study programme include limited technical competence of lecturers, students' skill gaps in technology, and limited course duration. To overcome these challenges, lecturers adopt strategies such as material condensation, project-based learning, differentiated instruction approaches, and the use of software that is easier for students to access and understand. Lecturers also encourage collaboration through group projects, regular monitoring, and evaluation that emphasises process as well as outcomes.